Mobile Time Tracker in Transportation Service: A Survey - et.al, Chee Ling, Thong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bus delay in transportation service is a common issue to be addressed. This issue is verified in a preliminary study conducted earlier among the bus riders. With the proliferation of mobile technology particularly in mobile application development, transportation service providertoday is able to address delay issue usingmobile application. In this study, a GPS based mobile application (App) is proposedto estimatetime arrival (ETA) of buses and an user acceptance test is used to verify the usability of the App. 76 bus riders have completed bus App testing and follow by a survey. The overall results show mobile time tracker is usable and able to solve issue of bus delay and reduce long waiting time. In future work, mobile time trackers associate with other ETA prediction models will be explored and issues such as ETA accuracy will also be addressed.